Peningkatan Psikoedukasi Baby Blues dan Kepedulian Sosial pada Bidan dalam Wilayah Kerja Dinas Kesehatan Kabupaten Musi Banyuasin - Mutia Mawardah; Mazidawati Mazidawati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Baby Blues Syndrome is a mild mood disorder syndrome that is often ignored by postpartum mothers, their families or health workers which in the end Baby Blues Syndrome can develop into depression and even psychosis which has a bad impact. The complexity of health problems, both physical and psychological during the reproductive period, especially in postpartum mothers, of course requires comprehensive and integrated treatment and involves all elements from across programs and related sectors. Midwives as the forefront in health services have important roles, functions and competencies in providing midwifery care to women during the pre-pregnancy, pregnancy, delivery and postpartum period. However, for health service efforts and care for the psychological health of postpartum mothers, especially health services related to psychological adaptation and psychological disorders experienced by mothers during the postpartum period are still not optimal. Therefore, it is necessary to empower and develop midwives as a potential group that plays an important role in providing care or health services for the health of mothers and their babies, both physically and psychologically. In this Independent Real Work Lecture (KKN-M) the author held an activity to Increase Baby Blues Psychoeducation and Social Awareness for Midwives in the Work Area of ??the Musi Banyuasin District Health Office as an effort to increase the role and social care of midwives as an effort to prevent baby blues. syndrome in postpartum mothers in Musi Banyuasin Regency.